Круиз Белоснежки: [повесть] / Вадим Поситко - Поситко Вадим Николаевич (Роман для девочек, 2003)
Экземпляры: ф.7 (2003) / Инвентарный номер: 45708 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: П 61 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-44